Pengaruh Islamicity Performance Index Terhadap Profitabilitas Bank Umum Syariah Indonesia Periode 2014-2018 - Mayasari, Firda Alia (Kompartemen : Jurnal Ilmiah Akuntansi, 2020)
This study focuses on the purpose of analyzing the effect of the Islamicity Performance Index which will be proxied by the Profit Sharing Ratio, Zakat Performing Ratio, Equitable Distribution Ratio and Islamic Income VS Non-Islamic Income Ratio on the profitability of Islamic Commercial Banks in Indonesia. This study uses 7 samples of Islamic commercial banks in Indonesia using the annual financial statements from the period 2014-2018. The sample in this study was selected using the Purposive Sampling Method. While the method used for data analysis in this study uses the Common Effect Model analysis panel data regression. The results of the analysis in this study indicate that the profit sharing ratio, equitable distribution ratio, and Islamic Income vs. non-Islamic Income variables have no effect on Return on Assets (ROA). As for the zakat variable Performing ratio has a positive and significant effect on Return on Assets (ROA). Keywords: Islamicity Performance Index, Profitability.